دور الشبابيك الآلية في تطور المعاملات المصرفية الإلكترونية في الجزائر - معطاالله محمد (جامعة الوادي University Of Eloued, 2024)
يهدف هذا المقال إلى دراسة وتحليل واقع استخدام الشبابيك الآلية وتقييم مساهمتها في تطور المعاملات المصرفية الإلكترونية في الجزائر، ولتحقيق ذلك اعتمدت الدراسة على وصف وتحليل مختلف الإحصائيات والمعطيات الخاصة بهذا الموضوع. وقد خلصت الدراسة إلى مجموعة من النتائج أهمها ازدياد عدد الشبابيك الآلية في الجزائر خاصة بعد جائحة كورنا مما أدى إلى ارتقاع عدد وحجم المعاملات المصرفية الإلكترونية واستخدام وسائل الدفع الإلكتروني، غير أن الشبابيك الآلية لا تزال تعاني من ضعف في تقديم الخدمات وانخفاض مستوى تواجدها في العديد من المناطق عبر الوطن. This article aims to study and analyze the reality of the use of automated windows and evaluate their contribution to the development of electronic banking transactions in Algeria, to achieve this, the study adopted to describe and analyze the various statistics and data on this subject. The study concluded a set of results, the most important of which is the increase in the number of automated windows in Algeria, especially after the Corona pandemic, which led to an increase in the number and volume of electronic banking transactions and the use of electronic payment methods, but the automated windows are weak in providing services and their number is few in the country.
The role of automated windows in the development of electronic banking transactions in Algeria
Keywords: شباك آلي; خدمة مصرفية إلكترونية; بطاقة إلكترونية; دفع إلكتروني; الجزائر; Automated windows; e-banking; e-card; electronic payment; Algeria